RELATIONSHIP BETWEEN KNOWLEDGE, ATTITUDE, AND PERSONAL HYGIENE WITH SCABIES INCIDENCE AT THE DAARUL ILMI CENGKLONG ISLAMIC BOARDING SCHOOL 2022 - Urpiyatul Ulya (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Scabies is a skin disease caused by the parasite Sarcoptes scabies hominis variety. The prevalence of scabies in Indonesia has decreased, data from the Indonesian Ministry of Health decreased from 2008 to 2013, as can be seen from the prevalence data for 2008 reaching 5.69% to 12.96%, 2012 reaching 4.9% to 12.95% and the latest data in 2013 reached 3.9% to 6%. The purpose of this study was to find out the relationship between knowledge, attitudes, and personal hygiene with the incidence of scabies at Daarul Ilmi Cengklong Islamic Boarding School in 2022. This research method is a quantitative analytic study using a cross-sectional approach with a sample of 72 people, sampling was carried out using the total sampling technique. Retrieval of data using a questionnaire. Data analysis used the Chi-square test (a = 0.05). Variable Results Gender and the incidence of scabies were not related (p-value 0.828). Variables related to the incidence of scabies were Age (p-value 0.035), Knowledge (p-value 0.000), Attitude (p-value 0.028), and Personal Hygiene (p-value 0.034). In conclusion, there is no significant relationship between gender and the incidence of scabies. There is a significant relationship between age, knowledge, attitudes, and personal hygiene and the incidence of scabies at the Daarul Ilmi Cengklong Islamic Boarding School.